Common variants in toll-like receptor family genes and risk of gastric cancer: a systematic review and meta-analysis - Al Othaim, Ayoub; Al-Hawary, Sulieman Ibraheem Shelash; Alsaab, Hashem O.; Almalki, Sami G.; Najm, Mazin A. A.; Hjazi, Ahmed; Alsalamy, Ali; Firras Almulla, Abbas; Alizadeh, Hamzeh (Frontiers in Genetics, 2023)
Background: Growing studies have suggested the relationship between single nucleotide polymorphisms (SNPs) in toll-like receptors (TLRs) genes and gastric cancer (GC) susceptibility, however, the available evidence remained contradictory. This meta-analysis aimed to comprehensively evaluate whether the SNPs within the TLRs family are related to GC development.The PubMed, Scopus, and China National Knowledge Infrastructure (CNKI) were systematically searched up to May, 2023 to obtain the pertinent publications. Pooled odds ratios (OR) and 95% confidence intervals (CIs) were applied to examine the associations using the random-effects model.Results: A total of 46 45 studies with 26,26825,831 participants (Cases: 11,518308; controls: 14,750523) examining the relation of 19 18 different SNPs in the TLRs family to GC were analyzed. TLR-2 rs3804099 T>C was protective against GC risk under the dominant (OR= 0.79; 95%CI: 0.62-0.99) and allelic (OR= 0.82; 95%CI: 0.70-0.97) models. In contrast, Vvariations in TLR-4 rs4986790, TLR-4 rs4986791, TLR-5 rs5744174, TLR-9 rs5743836, and TLR-9 rs187084 were significantly associated with increased risk of GC in different genetic models. A significant positive relationship between TLR-1 rs4833095 and odds of GC was also identified for Caucasians. No significant association was detected for TLR-2 -196 to -174de (Delta22), TLR-2 rs3804100, TLR-4 rs11536889, TLR-4 rs11536878, TLR-4 rs2770150, TLR-4 rs10116253, TLR-4 rs1927911, TLR-4 rs10983755, TLR-4 rs10759932, TLR-4 rs1927914, TLR-9 rs352140, and TLR-10 rs10004195.These findings indicate that SNPs in TLR-2 rs3804099 T>C may play a protective role in gastric carcinogenesis, while, variations in TLR-4, TLR-5, and TLR-9 genes were found as potential risk factors of for GC.